Pengaruh Gaya Kepemimpinan dan Kepuasan Kerja terhadap Kinerja Karyawan PT. Pelindo Cabang Bali - Wicaksono, Bimo Satria; Murdani, Ketut; Widiana, I Nyoman Wahyu (Universitas Pahlawan Tuanku Tambusai, 2024)
Employee job satisfaction is an important aspect or role in improving company performance with the various benefits it offers, such as completing tasks on time, reducing the risk of loss, and minimizing absenteeism and employee turnover. The purpose of this research is to evaluate the influence ofileadership style and job satisfaction on employee performance at PT. Pelindo Bali Branch. This research uses quantitative methods. The research population consisted of 35 respondents. The results of the analysis show that leadership style partially has a significant effect on employee performance (p = 0.014), with an influence of 29%. Apart from that, job satisfaction also has a significant effect on employee performance (p = 0.029), with an effect of 27%. Simultaneously, leadership style and job satisfaction simultaneously have a significant effect on the performance of PT employees. Pelindo Bali Branch (F = 0.000 < 0.05), with a total influence reaching 62.6%. This research provides an understanding of the importance of paying attention to leadership style and increasing job satisfaction to improve employee performance. The implication of this research is the need for companies to develop strategies that pay attention to these aspects in order to achieve competitive advantage through human resources that are more productive and actively involved in achieving organizational goals.